Młodzi Lubuszanie w przestrzeni społecznej szkoły gimnazjalnej = Young Lubuskie inhabitants witin the junior high school social space - Lipińska-Lokś, Jolanta; Winczura, Barbara (Zielona Góra: Lubuskie Towarzystwo Naukowe)
A school is the place where children and teenagers spend most of their lives fulfilling compulsory education and interacting with other participants of the educational process: peers, teachers, other school staff and supportive parents. For the proper development (especially emotional and social) of a young generation it is important that this school social space is a valuable environment for students who derive satisfaction from staying in school. Due to the importance of the problem of student situation at school, the research covered their relationship with peers, interaction with teachers and the role of parents in school life. Presented results indicate the complexity of a target state which requires modifications in many aspects.
Keywords: szkolnictwo ponadpodstawowe; młodzież gimnazjalna; gimnazjaliści; gimnazjum; województwo lubuskie; przestrzeń społeczno-kulturowa